Pelatihan Perawatan Lansia Dengan Demensia: Implementasi Asuhan Keperawatan Di Komunitas - Sri Ariyanti; Rachmat Ramli; Trimaya Cahya Mulat; Rahmat Pannyiwi (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
The increasing elderly population in Indonesia has led to a rise in dementia cases, requiring special attention in caregiving. Families and communities play an essential role in maintaining the quality of life of older adults with dementia through community-based nursing care. This community service program aimed to improve family knowledge and skills in providing nursing care for elderly people with dementia in the working area of Puskesmas X. The methods used included interactive lectures, demonstrations, group discussions, and leaflet distribution. Participants consisted of 25 families caring for elderly individuals with mild to moderate dementia. The results showed an 82% increase in participants’ knowledge based on pre- and post-test evaluations. Participants were able to understand the basic concepts of dementia, effective communication techniques, and elderly care principles. This program strengthens the role of families in maintaining cognitive function and emotional well-being among the elderly in the community.